Nadania obywatelstwa rzymskiego w Hiszpanii w okresie wojny sertoriańskiej - Ładoń, Tomasz (In Gremium. Studies in History, Culture and Politics, 2014)
The Granting of the Roman Citizenship in Spain during the Sertorian War In the years 80-71 BC in Spain played out a fierce war between the rebellious Marian governor, Quintus Sertorius, and Senate commanders, Q. Metellus Pius and Cn. Pompeius. An important issue for both sides during this conflict was to gain sympathy of local peoples and one of the elements of such a policy was giving the Roman citizenship to the population of the province. In the first part of the article the author considers the possibility of granting the Roman citizenship by Sertorius to representatives of the Spanish aristocracy. The Author does not deny this possibility, but he draws attention to the fact that the Marian governor could not abuse this privilege because he had to bear in mind the real possibility of fulfillment of promises made. In the second part of the text the author discusses the granting of the Roman citizenship by the Senate commanders. They are much better attested in the source material, especially when it comes to the granting citizenship by Pompey. They have been confirmed by the authorities in Rome specially carried out in this case law (lex Cornelia Gellia). It seems, however, that the granting of the Roman citizenship did not have a mass character and concerned mostly to the romanized population of Spain. The Roman citizenship was a reward for those among the inhabitants of Spain, who after moving there the Roman civil war not only kept fidelity to the Sullans, but also deserve a fight against Sertorius.